(3QSGdI Yf GdMLQ hJUQjags
(3ChdgG (B:s
(3GYde Gf gPG GdMLQ gh LhgQ hGMO hdcfg jfbSe bSejf hScdjf eNJdajf CMOgeG QhMGfi hGdBNQ LSeGfi s
(3BNQgG (B:s
(3hGdb hGMOkG Ydi eGFI RgQI Ch eTJQi jchf beQkG NGdUkG HEPf Gddg JHGQc hJYGdi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B33 - (3U(B34s
(3GdfSNI HgG MhGTs
(3cJHgG CMO GdadGSaI hCQSd HgG Edi JdejPgs
(3jdjgG hQbI HYV Gdfbhd hGdahGFO ai UfGYI GdcjejGA hJOHjQ GdCMLGQ ef HYV eKd cJGH cHg hcJGH Pi Gdfhf GdeUQi hef cdGe GHf hMTjI hCHi Yhf Hf Nda GdMhGQi hLGHQ Hf MjGf hGdYPGbQi hCHi HcQ GdQGRi hGdcQeGfis
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs